Human Resources Management: Efforts to Increase the Professionalism in Islamic Boarding Schools - Norhidayah Ridhawati (Journal on Education, 2024)
Human Resources (HR) are a central factor in an educational institution. However, the fundamental phenomenon that currently tends to occur in educational institutions is the existence of less qualified educators and education personnel (HR), including in Islamic boarding schools. The aim of this research is to describe human resource management for educators and education staff at the Nailul Autahr Islamic boarding school, Murung Raya Regency. As for the type and approach in this research, it is usedfield research (field research) with a qualitative approach, with the subject being Islamic boarding school leaders, ustadz and ustadzah as teaching staff. The results of this research are human resource management in educators and educational staff at the Nailul Authar Islamic Boarding School above which shows the importance of human resource management in Islamic boarding school educators and educational staff in order to produce quality human resources. Then, the ongoing human resource management starting from planning, organizing, mobilizing and supervising at the Nailul Authar Islamic Boarding School can be maintained and even improved in the future.